2016
DOI: 10.1007/s12199-016-0535-1
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of the relationship between diet and mental health in female university students enrolled in a training course for registered dietitians

Abstract: Proper education concerning their diets and reducing confectioneries in their daily lives might be beneficial for the mental health of female university students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…We used the GHQ scores as the dependent valuable, and age (years), BMI (kg/m 2 ), n-6/n-3 fatty acid ratio and sucrose (g). The n-6/n-3 fatty acid ratio was statistically significant by simple correlation analysis in our study, and other factors were considered to be clinically important based on our previous study [25]. As a result, n-6/n-3 fatty acid ratio (β: 0.230, p = 0.049) was found to be a determinant factor for the GHQ scores, even after adjusting for age (years), BMI (kg/m 2 ) and sucrose (g) in community dwelling Japanese women.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…We used the GHQ scores as the dependent valuable, and age (years), BMI (kg/m 2 ), n-6/n-3 fatty acid ratio and sucrose (g). The n-6/n-3 fatty acid ratio was statistically significant by simple correlation analysis in our study, and other factors were considered to be clinically important based on our previous study [25]. As a result, n-6/n-3 fatty acid ratio (β: 0.230, p = 0.049) was found to be a determinant factor for the GHQ scores, even after adjusting for age (years), BMI (kg/m 2 ) and sucrose (g) in community dwelling Japanese women.…”
Section: Resultssupporting
confidence: 57%
“…Although there are some reports of the relationship between diet and mental health [11,12,13,14,15,16,17,18,19,20,21,22], evaluation of diet surveys is not accurate or reliable, as expected. In addition, we previously investigated the link between diet and mental health in female university students enrolled in a training course for registered dietitians, who were thought to be more health conscious than average students [25], and found that the consumption of confections is associated with mental health [25]. However, in other ages, accurately and reliably evaluated, the link between diet and mental health remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…One study found a positive association of diet quality with positive emotional state, but no association with negative emotional state [ 72 ]. Studies using questionnaires reported unhealthy diets to be associated with bad mental well-being [ 52 , 73 , 74 ], as well as healthy diets to be associated with good mental well-being [ 52 , 74–77 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, this review focussed only on depression and anxiety, but no other aspects of mental health. This review assessed 16 cross-sectional studies, of which 14 fulfilled our inclusion criteria and have also been included in our review [ 44 , 47 , 48 , 50 , 53–55 , 58 , 59 , 73 , 82–84 ]. The results of this review were in line with our results, as the authors concluded that most of the cross-sectional studies found a positive influence of healthy diets on depression and anxiety, with a few studies finding inconsistent results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation